Transformation of oil palm mesocarp fiber to convertible materials in water at subcritical state - Mahandran, Sanggithapriya (2020)
In this research, water at subcritical state was studied as an alternative way to breakdown oil palm mesocarp fibre (OPMF) by analysing their structural and compositional changes at different reaction temperature. High ion products of water in subcritical conditions and the dielectric constant of water at temperature above 200°C makes water to behave as acid catalyst and environmentally friendly solvent. The decomposition of OPMF using subcritical water (Sub CW) method has been carried out at reaction temperature ranging from 200°C to 300°C and with constant reaction time of 5 min using a batch stainless-steel tube as reactor. The highest oil yield was obtained at 240°C with result values 219.6 mg g-1 dry OPMF due to the behaviour of water to act like ethanol solvent at 240°C (ɛ= 27.0). High-performance liquid chromatography (HPLC) analysis identified that the highest number of monosaccharides such as glucose and fructose presented at 240°C was due to optimum condition for hydrolysis process with sugar yield, 22.17mg g -1 dry OPMF. Moreover, morphological and particle size analyses proven that water at Sub critical state ease hydrolysis process occur as the Sub CW temperature increase to 240°C. When the reaction temperature gets higher than 240°C, cellulose of OPMF degrades through pyrolysis process. Increase in Sub CW reaction temperature decreases yield of solid from 0.286 g g-1 dry OPMF at 200°C to 0.037 g g-1 dry OPMF at 300°C. Thus, Sub CW at 240°C was able to extract optimum oil and sugar at high yield and reduces solid residue from mesocarp fibre with the absence of any chemical solvent.